(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
The object of the study is the external market for doing business. The purpose of the study is to determine the factors of choosing an external market for doing business. Research results: the factors influencing the strategic decision-making process are presented, the main motives for business expansion abroad are revealed. Entrepreneurs and heads of organizations should make rational decisions, but there is always a risk of incurring various costs. Thus, there is a difficult task: it is necessary not only to make a decision about the company’s development of a new market, but also about the way to enter it.